Constructing a causal attribution scale for physical education teachers for physical education lessons in maysan governorate - Al-Krizi, Maitham Mutair Hamidi (STKIP Taman Siswa Bima, 2025)
Background. Relationship between attribution and some of the explanations that the individual provides for his success and failure. He attributes this success and failure to the presence of four basic factors such as ability, effort, difficulty of the task, and luck. Objectives. The research aims to build a causal attribution scale for physical education teachers in Maysan Governorate. Methods. The researcher used the descriptive approach with a sample method. The study was applied to a sample of (134) educational staff, including male and female physical education teachers in Maysan Governorate. The sample of the exploratory study amounted to (29) participants, and the main study amounted to (205) participants. They were selected randomly. The causal attribution scale was built (prepared by the researcher) and appropriate statistical treatments were used. (5) sources were identified, namely confronting anxiety - emotional arousal - self-confidence - mental imagery - emotional balance, which represent the main axes of the causal attribution scale for physical education teachers in Maysan Governorate. Results. Existence of a strong consistency relationship between the questions posed and dimension to which phrase relates to scale of causal attribution axes, where highest consistency was recorded in the third axis (self-confidence), question No. (13), the least consistency between the questions posed and dimension to which phrase relates is in the second axis (emotional arousal), question number (17), which reached (167). Conclusion. The study concluded that these axes can be adopted to identify the arithmetic averages and standard deviation of physical education teachers and instructors. It concluded that there are standard scores for the causal attribution axes scale and recommended the necessity of using these axes as an indicator to identify the causal attribution of physical education teachers and instructors in Maysan Governorate.